CHEMICAL COMPOSITION OF ESSENTIAL OILS OF FOUR PHLOMIS SPECIES FROM TURKEY: A CHEMOTAXONOMIC APPROACH - Dogan, Gulden (Bangladesh Botanical Soc, 2017)
The chemical composition of the essential oils of dried aerial parts of four Phlomis species; P. rigida, P. oppositiflora, P. linearis and P. kurdica analyzed by GC and GC-MS. Forty, 32, 42 and 41 components were identified representing 94.5, 95.1, 92.8 and 92.9% of the oils, respectively. The main compounds were determined as epizonaren (14.3%), delta-cadinene (11.0%), spathulenol (10.7%), alpha-copaene (7.5%) and beta-bourbonene (5.4%) in P. rigida; germacrene D (22.7%), germacrene B (15.0%), bicyclogermacrene (9.0%), camphor (5.9%) and caryophyllene oxide (5.4%) in P. oppositiflora; germacrene D (17.3%), chrysanthenyl acetate (5.9%), trans-chrysanthenol (5.8%) and 2-pentadecanone (5.2%) in P. linearis and germacrene D (36.5%), beta-farnesene (14.5%), beta-pinene (10.5%) and bicyclogermacrene (7.2%) in P. kurdica. The results were discussed in view of natural products and chemotaxonomy.
Keywords: Phlomis; Essential oil; Chemotaxonomy; GC-MS; Epizonaren; Germacrene D